The role of minority education in the expansion of the functions of Hungarian landscape houses - Szeidl, Klaudia (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
The stages of Hungarian cultural life can be seen in landscape houses, which hold and demonstrate the local community's appreciation of ancient times and the culture of the local ethnicities in a museum-like environment. The uniqueness of the Hungarian landscape house network is noted in the fact that in 2002 they were nominated on the tentative list of UNESCO World Heritage sites. In the lifecycle of the landscape houses, there has been a change in paradigm, owing to which the museum function has lost its central role. Our research focuses on a survey of the efficiency of the cooperation between landscape houses and minority educational institutions. In the framework of such cooperation, the present state of the landscape houses and their programme supply have been mapped. In terms of feedback, students participating in minority education were asked about their opinion on and their experiences surrounding landscape houses.
Keywords: kulturni turizem; Madžarska; manjšinsko šolstvo; model uporabe podeželskih hiš; mreža tradicionalnih madžarskih podeželskih hiš; širitev ponudbe